Evaluating Properties of Blended and High Volume Fly Ash Bottom Ash (FABA) Concrete in Peat Water - Monita Olivia Olivia; Alfian Kamaldi; Ismeddiyanto; Gunawan Wibisono; Edy Saputra (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2023)
FABA is a by-product of coal combustion in power plants comprising fly ash (FA) and bottom ash (BA) in ratios of 80/20. Fly ash has great potential as a mineral ingredient in concrete, while bottom ash compromises its strength and durability. However, both materials are used to improve the strength and durability of structures in sulfate, chloride, and acidic environments. This research evaluated the properties of blended and high-volume FABA concrete, such as the strength, porosity, weight loss, and sorptivity in organic acidic peat water. OPC (Ordinary Portland Cement) was compared to the blended concrete containing 25% FABA and its high-volume containing 50% and 75% FABA with target strengths of 15, 21, and 29 MPa. The compressive strength of blended and high volume FABA increased during the immersion period, while the porosity and sorptivity rates decreased. Furthermore, the strength of the OPC concrete declined at 28 days, with a gradual marginal weight loss of 5% observed in all mixes. This research suggested that blended and high-volume FABA has potential as a construction material in an acidic peatland environment.